Optimal biomass transportation model - Chu, K. M.; Abdul Halim, Abdul Razik (Universiti Malaysia Pahang, 2021)
The transportation represents a key proportion of the operational cost for the biomass industries worldwide. As biomasses are mainly carried by trucks for parts of the transportation, the focus of this paper is on the transport of treated and untreated biomass (rice husk, empty fruit bunch, and woody biomass) by large, medium and small trucks. The objectives were to formulate biomass transportation model for transporting treated and untreated biomass resources and to obtain optimal result for selecting the best transportation mode. By screening of biomass types, locations for treated and untreated biomass resources and screening of suitable transportation mode used, the important model parameters were obtained and linear programming for minimizing overall transportation costs was formulated. General Algebraic Modelling System (GAMS) software was used to solve the optimization formulations. From the optimization result obtained by using GAMS, large truck was selected to be the best transportation mode for treated, untreated and hybrid biomass since it showed minimal overall transportation cost.